Light Scattering by Systems of Particles Null-FieldMethodwithDiscrete Sources: Theory and Programs - Doicu, Adrian; Wriedt, Thomas; Eremin, Yuri A.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2006)
Light Scattering by Systems of Particles comprehensively develops the theory of the null-field method, while covering almost all aspects and current applications. The "Null-field Method with Discrete Sources" is an extension of the Null-field Method (also called T-Matrix Method) to compute light scattering by arbitrarily shaped dielectric particles. This book incorporates FORTRAN programs and exemplary simulation results that demonstrate all aspects of the latest developments of the method. Worked examples of the application of the FORTRAN programs show readers how to adapt or modify the programs for their specific application.
Basic Theory of Electromagnetic Scattering -- Null-Field Method -- Simulation Results -- Spherical Functions -- Wave Functions -- Computational Aspects in Effective Medium Theory -- Completeness of Vector Spherical Wave Functions.
Keywords: Physics; Optics; Optoelectronics; Plasmons (Physics).; Engineering; Physics; Optics, Optoelectronics, Plasmonics and Optical Devices; Engineering, general; Electronic books